indonesia SYSTEMATIC LITERATURE REVIEW TENTANG PENERAPAN TEKNOLOGI BLOCKCHAIN PADA BIDANG KEUANGAN - Ramadan, Zeinan; Supriadi, Fidi; Indra Junaedi, Dani (TeIKa, 2025)
Distributed ledger technology, better known as blockchain, has emerged as a promising breakthrough in supporting financial inclusion, especially for populations that are not covered by conventional financial frameworks. This paper aims to investigate the contribution of blockchain in boosting financial inclusion compared to the established financial system through a systematic literature review approach. This paper summarizes literature from leading academic databases to identify key findings on the benefits, constraints, and prospects of blockchain development in the financial sector. The analysis shows that blockchain can expand the accessibility of financial services, reduce transaction costs, and provide greater transparency and protection. However, several challenges arise such as the lack of regulatory framework, knowledge disparity, and issues of scalability and interoperability. The conclusion of this review indicates that blockchain has significant potential to boost financial inclusion, but collaborative efforts from governments, corporations, and technology innovators are needed to overcome these obstacles. This paper provides an in-depth understanding of the opportunities and challenges of blockchain implementation and recommendations for further research.